From needs assessment to needs analysis - Christensen, B. D. (Performance Improvement, 2018)
The steps to go from a performance problem to a value-added solution can be tricky when the terms needs assessment, needs analysis, and training needs analysis, which describe key steps in the process, are misunderstood and used incorrectly. The transition from needs assessment to needs analysis, along with the follow-on steps to improved performance with the inclusion of gap prioritization and business requirement definition, provide a systematic approach to achieving positive results.